The Influence of Using Division Boards towards Improvement of Students' Islamic Elementary School Arithmetic Skills - Devicha Dwi Mahmudah; Khurin’In Ratnasari (AR-RIAYAH: Jurnal Pendidikan Dasar, 2025)
This research investigates the students' inability to execute mathematical division calculations in elementary school. Learning through lecture methods, giving examples, and exercises is frequently monotonous. So, mathematics is considered a subject that is complicated and difficult to understand. The purpose of the research is to assess the impact of using division boards in enhancing students' arithmetic skills, especially regarding basic and operational arithmetic aspects. Quantitative approach uses a quasi-experimental nonequivalent control group design. The sample includes 30 students separated into control and experimental groups. Data collection techniques are observation, interviews, documentation, and tests, while data analysis is conducted using normality tests, homogeneity tests, and independent t-tests. The results indicate that there is a significant difference between the experimental and control groups, which has a significance value of 0.000 < 0.05. These findings demonstrate the effectiveness of the division board media in enhancing students' arithmetic skills and in encouraging student to participate actively in learning activities. This study recommends the use of concrete media as instructional tools that are relevant to the cognitive development stages of students, particularly in understanding abstract mathematical concepts such as division.